Studies of Genetic Variability of Tomato (Solanum lycopersicum L.) Hybrids under Protected Environment - Waiba, Kanchhi Maya; Sharma, Parveen; Kumar, Kasi Indra; Chauhan, Shivani (International Journal of Bio-resource and Stress Management, 2021)
A study was conducted to estimate genetic variability among horticultural traits and to evaluatethese hybrids for protected environmental cultivation during spring-summer season, 2019 (April-September). Twelve hybrids of tomato were evaluated under modified naturally ventilated poly-house at the Vegetable Research Farm, Department of Vegetable Science and Floriculture, Chaudhary Sarwan Kumar Himachal Pradesh Krishi Vishvavidyalaya following Randomized Complete Block Design (RBD) with three replications, Palampur, Himachal Pradesh, India. Based on the mean performance, hybrid CLN2126×CLN1314G was found promising for yield plant-1 (4.37 kg) yield m-2 area (26.24 kg), TSS (6.53 °B), days to 50% flowering (26.66 days), days to first picking (67.33 days), number of fruits per plant (64.01), inter-nodal length (17.71 cm), number of nodes plant-1 (16.70 nodes) and plant height 316.87 cm). So, an ideal plant type producing a higher yield per plant will be the one having traits like a higher number of fruits per plant, and lesser days to first picking. It is concluded that the hybrid combination CLN2126×CLN1314G is promising for these traits. This can be included for multi-locational testing in different agro-climatic zones of Himachal Pradesh under protected environment.